2011
DOI: 10.1590/s0100-69162011000600013
|View full text |Cite
|
Sign up to set email alerts
|

GPS receivers for georeferencing of spatial variability of soil attributes

Abstract: ABSTRACT:The characterization of the spatial variability of soil attributes is essential to support agricultural practices in a sustainable manner. The use of geostatistics to characterize spatial variability of these attributes, such as soil resistance to penetration (RP) and gravimetric soil moisture (GM) is now usual practice in precision agriculture. The result of geostatistical analysis is dependent on the sample density and other factors according to the georeferencing methodology used. Thus, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
0
3
1
2
Order By: Relevance
“…In a certain way, these results are similar to those found for this study, in which there is also a variation in the accuracy of GPS receivers to carry out samplings of RP and WC, which may come to influence future soil operations in rates variables, under or overestimating the compacted layers scattered around the area. When ROSALEN et al (2011) studied the GPS receivers for the georeferencing of soil attributes spatial variability, they found spherical models using navigation and geodetic GPS for the resistance to penetration and exponential, using the same receivers for the WC in layers of 0-0.10m, these results are different from this study in which the navigation receivers showed e xponential and Gaussian model for the navigation GPS in relation to the RP.…”
Section: Resultscontrasting
confidence: 84%
“…In a certain way, these results are similar to those found for this study, in which there is also a variation in the accuracy of GPS receivers to carry out samplings of RP and WC, which may come to influence future soil operations in rates variables, under or overestimating the compacted layers scattered around the area. When ROSALEN et al (2011) studied the GPS receivers for the georeferencing of soil attributes spatial variability, they found spherical models using navigation and geodetic GPS for the resistance to penetration and exponential, using the same receivers for the WC in layers of 0-0.10m, these results are different from this study in which the navigation receivers showed e xponential and Gaussian model for the navigation GPS in relation to the RP.…”
Section: Resultscontrasting
confidence: 84%
“…Several types of information have been used to delineate management zones, such as: terrain attributes, electrical conductivity, soil resistance to penetration, chemical soil attributes, crop indices like NDVI (Normalized Difference Vegetation Index ), and crop yield maps (FRAISSE et al, 2001;JIANG et al, 2011;ROSALEN et al, 2011;DELALIBERA et al, 2012). Among these types of information, some studies in Brazil (MOLIN, 2002;AMADO et al, 2007) have defined management zones based on yield maps from data collected over time.…”
Section: Introductionmentioning
confidence: 99%
“…Essa variabilidade pode ser ocasionada por diversos fatores, desde a forma de preparo do solo até a heterogeneidade do próprio material de origem (Cavalcante et al, 2007;Dalchiavon et al, 2012). O advento do Sistema de Posicionamento Global (GPS) e a utilização de técnicas geoestatíticas tornam possível a compreensão da variabilidade espacial das características do solo e das plantas possibilitando a partir de dados amostrados, inferir valores a pontos intermediários utilizando-se as técnicas do semivariograma e da interpolação (Rosalen et al, 2011).…”
Section: Introductionunclassified